THE USE OF TIME-RELATED PHRASEOLOGICAL UNITS IN BOTH ENGLISH AND RUSSIAN LANGUAGES - Mukimjon , Akhunov; Iskhakova , Aliya Ildarovna (Educational Research in Universal Sciences, 2023)
“The study explores the utilization of phraseological units related to the theme of time in English and Russian languages, highlighting differences in translation and usage. It delves into the distinct ways these phrases are employed in both languages, elucidating the purposes behind their usage. The thesis provides examples of time-related phrase usage in both English and Russian to illustrate contextual variations. Ultimately, the research aims to draw insightful conclusions regarding the cultural and linguistic nuances embedded in the expressions of time in these languages.”